Growth and mortality of Green Mussel Perna viridis farmed at Ambong Bay and Marudu Bay, Sabah, Malaysia - Irman Isnain; Bernardette Mabel Manjaji Matsumoto; Julian Ransangan; Shuhadah Mustapha (2020)
Asian green mussel is commercially farmed in tidal waters in several enclosed bays in Sabah, Malaysia. In this study, two areas on the west coast of Sabah – Ambong Bay and Marudu Bay – were selected for the monitoring of the growth and mortality rates of green mussels farmed in suspension raft. Both growth and survival rates were then correlated with physicochemical parameters (dissolved oxygen, pH, salinity, temperature, water transparency, chlorophyll-a), nutrients (phosphate (PO4 3-), ammonia (NH3 -N), nitrate (NO3 -N) and nitrite (NO2 -N) and condition index of mussel from each study site, as well as between the study sites. The twelve-month growth study (September 2017 to August 2018) was started with a total of 180 mussel specimens (90 at each site). The initial size (mean) of the mussel seed used was 47.7 ± 3.5 mm and 51.1 ± 3.9 mm for Marudu Bay and Ambong Bay, respectively. Mussels in Marudu Bay attained mean size of 73.47 ± 11.05 mm (SGR 0.17% ± 0.22) compared to 64.05 ± 7.44 mm (SGR 0.11% ± 0.22) for Ambong Bay at the end of the experiment. The cumulative mortality rates were 9.2% ± 4.9 and 55.5% ± 30.0 for Marudu Bay and Ambong Bay, respectively. The Pearson correlation indicated a significant positive relationship between mortality and water transparency (r = 0.684, p<0.01). There was a significant negative relationship between ammonia in seawater and mussel mortality (r = -0.561, p<0.01), as well as significant negative relationships between nitrate and growth (r = -0.480, p<0.05) and mortality (r = -0.460, p<0.05), as indicated by Spearman’s Rank-order Correlation analysis. Overall, the growth performance of green mussels farmed in Marudu Bay was better than in Ambong Bay, however, the mortality of mussels in Ambong Bay was higher.